Frequency of Vaginal Infection among Pregnant Women with Vaginal Discharge - Raza, Andaleeb; Najma Bibi; Sadia Anwar; Raheela Bano; Saima Umar; Sadaf Saifullah (Annals of Punjab Medical College, 2022)
Background: Pregnant women are at risk of adverse outcomes from vaginal infections, which can be common and potentially serious. There is, however, a lack of information on the prevalence of vaginal infection and risk factors leading in different populations. Objective: To determine the frequency of vaginal infections among pregnant women and its association with demographic and clinical characteristics. Study Design: Cross-sectional study. Settings: Women and Children Hospital, Gomal Medical College, Dera Ismail Khan Pakistan. Duration: from September 1, 2020 to February 28, 2021. Methods: The study included 193 pregnant women who experienced vaginal discharge by non-probability consecutive sampling and sample size of 193 was calculated using WHO software with a 95% confidence interval. A variety of variables were recorded, including data on vaginal infection. Results: The results indicate that 52.8% of the women in this sample had experienced a vaginal infection. The mean age of the women was 28.088±3.11 years, the mean gestational age was 23.559±3.88 weeks, the mean parity was 1.378±1.33, the mean weight was 70.787±5.69 kg, and the mean discharge duration was 7.735±1.91 days. Age and parity were significantly associated with vaginal infection, but not with gestational age, weight, or duration of discharge. Conclusion: This study indicates a high prevalence of vaginal infections in pregnant population. More than half of the sample was affected by vaginal infection, which was common and significant. Vaginal infections were more common in young age, low parity and at early gestation.